The sound of love. Music and affect in Filip Dzierżawski's 'Miłość'. Issue 2 (4th May 2019) - Szarecki, Artur
Abstract: In the 1990s Poland, a young generation of musicians attempted to reinvent jazz in a spirit of playful experimentation. Miłość, meaning 'love', was one of the pivotal bands in this movement, which came to be known as yass. Filip Dzierżawski's documentary of the same title offers a candid look on the intimate and difficult relations between Miłość's musicians, as they discuss a possible reunion in 2008. As such, it provides an opportunity to reflect on how the emotional bond that connects them impacts their music and their capacity to play together. Therefore, in this paper, I employ affect theory to provide a rereading of the film's plot and audiovisual content. Specifically, I argue that through its combination of archival footage, interviews, and depiction of real-time interaction during the band's rehearsal, Dzierżawski's documentary encourages us to think of music making in terms of affect, that is, as emerging from intensive relations between different entities as they come into contact and undergo a series of transformations in their capacities to affect and be affected by each other and their environment.